Crime and police personnel in Malaysia: an empirical investigation - Habibullah, Muzafar Shah; Abdul Hamid, Baharom; Tan, Keat Siang (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2013)
The economic theory on crime behavior proposed by Becker (1968) suggests that increase in the number of policemen can deter crimes. However, recent studies found a positive relationship between police personnel and crime rates. The purpose of the present study is to investigate the effect of police personnel on 15 categories of crime rates in Malaysia for the period 1973 to 2005 by using the vector error-correction model. Our results suggest that 8 categories of crime rates support Becker’s crime economic theory, while 6 categories of crime support the “long-run natural rate of crime” hypothesis.